Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1136/esmoopen-2017-000257
|View full text |Cite
|
Sign up to set email alerts
|

TPF induction chemotherapy increases PD-L1 expression in tumour cells and immune cells in head and neck squamous cell carcinoma

Abstract: BackgroundAntiprogrammed cell death-1/programmed cell death-ligand 1 (PD-1/PD-L1) therapies have demonstrated promising activity in advanced head and neck squamous cell carcinoma (HNSCC), with overall response rates of approximately 20% in unselected populations and survival benefit. Whether induction docetaxel, platinum and fluorouracil (TPF) modifies PD-L1 expression or tumour immune infiltrates is unknown.Patients and methodsPatients with locally advanced HNSCC treated at Gustave Roussy (Villejuif, France) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 43 publications
3
54
0
Order By: Relevance
“…In particular, it has recently been shown that PD‐L1 significantly increased on residual disease after NACT compared with baseline in a large retrospective cohort of patients with TN early BC . The induction of PD‐L1 expression by chemotherapy is consistent with observations in other cancer types and with the notion that chemotherapy is able to induce an adaptive immune response through various mechanisms, including immunogenic cell death and the activation of the damage response c‐GAS/STING . Indeed, it has been shown that CT may boost the immunogenicity of the tumor by increasing tumor immune infiltrate from baseline to post‐NACT samples, with a high rate of conversion from low‐TIL to high‐TILs tumor .…”
Section: Methodssupporting
confidence: 71%
See 1 more Smart Citation
“…In particular, it has recently been shown that PD‐L1 significantly increased on residual disease after NACT compared with baseline in a large retrospective cohort of patients with TN early BC . The induction of PD‐L1 expression by chemotherapy is consistent with observations in other cancer types and with the notion that chemotherapy is able to induce an adaptive immune response through various mechanisms, including immunogenic cell death and the activation of the damage response c‐GAS/STING . Indeed, it has been shown that CT may boost the immunogenicity of the tumor by increasing tumor immune infiltrate from baseline to post‐NACT samples, with a high rate of conversion from low‐TIL to high‐TILs tumor .…”
Section: Methodssupporting
confidence: 71%
“…It should also be noted that PD‐L1 stromal expression encompasses not only TILs but also macrophages and fibroblast‐like cells, thus further increasing the complexity of the biological role of PD‐L1 in possibly affecting response to immunotherapy .…”
Section: Methodsmentioning
confidence: 99%
“…PD-1 and PD-L1 expression currently remain the most significant tissue biomarkers. PD-L1 expression has been associated with postchemotherapy (docetaxel/platinum/5-fluorouracil regimen) status, 127 co-occurrence with p16 INK4 expression, 131 and poorer OS 124,126,128 (but improved RFS 125,129 and OS 125,130 ). Among these studies, associations between high PD-L1 expression and favorable OS were all demonstrated in post-surgery HNSCC patients.…”
Section: Predictive Tissue Markers For Egfrtargeted Therapymentioning
confidence: 99%
“…Neoadjuvant chemotherapy may up-regulate the expression of PD-L1 in lung squamous cell carcinoma as was recently published [15]. A recently published study showed increased PD-L1 expression on tumor cells in head and neck squamous cell carcinoma treated with TPF induction chemotherapy [16]. Another case report showed a decrease in PD-L1 level in NSCLC after chemotherapy including gemcitabine and platinum [17].…”
Section: Discussionmentioning
confidence: 94%